EFQM in Academic Libraries: The Application of a Quality Management Model at the University of Cyprus Library - Stavridis, Stefanos; Tsimpoglou, Filippos (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
In December 2009 the University of Cyprus Library became the first library in Greece and Cyprus to achieve the EFQM Recognized for Excellence distinction, awarded by the European Foundation for Quality Management. That was the Library’s first engagement in quality management. The program helped the Library both to start processes that will improve its administration and to shape a very concrete perception of the need and methodology of self-assessment. The purpose of this paper is to contribute to the discussion on adopting EFQM in academic libraries by highlighting the main points of this experience and by drawing conclusions regarding the benefits gained and challenges encountered.